Biotechnology and Bioengineering 2019
DOI: 10.5772/intechopen.84643
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design, Fabrication and Evaluation of Resorbable Fiber-Based Tissue Engineering Scaffolds

Abstract: The use of tissue engineering to regenerate viable tissue relies on selecting the appropriate cell line, developing a resorbable scaffold and optimizing the culture conditions including the use of biomolecular cues and sometimes mechanical stimulation. This review of the literature focuses on the required scaffold properties, including the polymer material, the structural design, the total porosity, pore size distribution, mechanical performance, physical integrity in multiphase structures as well as surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 114 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…The drapability of warp-knitted spacer fabric scaffolds also makes them attractive candidates in complex tissue engineering applications such as muscle-tendon junctions. 71…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drapability of warp-knitted spacer fabric scaffolds also makes them attractive candidates in complex tissue engineering applications such as muscle-tendon junctions. 71…”
Section: Discussionmentioning
confidence: 99%
“…The drapability of warp-knitted spacer fabric scaffolds also makes them attractive candidates in complex tissue engineering applications such as muscletendon junctions. 71 With only few engineered tissues successfully used for clinical purposes, 54 the present work describes the design and manufacturing of a 3D textile scaffold able to support cell attachment and growth, and gives insights on the properties of bioabsorbable polymeric yarns during degradation and their potential effects on cell behaviour, thus contributing to the further development of bioabsorbable tissue engineering scaffolds.…”
Section: Papermentioning
confidence: 99%
“…Cotton materials have been explored for the fabrication of scaffolds for tissue-engineered applications. King, Chen [ 106 ] reported that woven fabrics have effective mechanical strength and structural stability due to properties such as porosity and thickness. A porous structure of a tissue-engineered scaffold derived for fibre is shown in Figure 8 .…”
Section: Environmental Impact Of Cotton Wastesmentioning
confidence: 99%
“…Synthetic degradable polymers, such as poly(lactic acid) (PLA), poly(glycolic acid) (PGA), polycaprolactone (PCL) or copolymers, have been widely researched and used in class 3 medical devices because of their superior mechanical strength, biodegradability and low cytotoxicity. 5,6 However, they have also been implicated to elicit chronic inflammation that does not favor vascular regeneration. 7 On the contrary, natural polymer-hydrogels have been widely used in tissue engineering and regenerative medicine due to their bioactivity that rapidly resolves acute inflammation and promotes tissue cell ingrowth.…”
Section: Introductionmentioning
confidence: 99%
“…6,13 The knitting conduit was flexible and compliant, making it suitable for the vascular graft application. 5,6,13 Although textiles fabricated from PLA yarn have shown satisfactory mechanical robustness and radial compliance, they lack bioactivity, such as cell binding motifs to facilitate cell adhesion. It has also been reported that PLA prolongs the local inflammatory response, elicits a mild foreign body reaction, and retards tissue regeneration, especially in vascular applications.…”
Section: Introductionmentioning
confidence: 99%